Peran Director of Photography dalam Pendekatan Visual dan Naratif Feature Audiovisual "Setu Babakan: Rumah Betawi Hari Ini" - Ridha Elsarah Effendi; Siti Noorhayati Fajrian; Encang Saepudin; Kurnia Lucky Fadillah (Realisasi : Ilmu Pendidikan, Seni Rupa dan Desain, 2026)
The rapid development of Jakarta has led to the declining presence of traditional Betawi houses, highlighting the need for media that can introduce and support cultural preservation efforts. Audiovisual feature productions serve as an effective communication medium by combining visual, audio, and narrative elements to deliver cultural information in an engaging manner. This study aims to analyze the role of the Director of Photography in developing visual and narrative approaches in the audiovisual feature Setu Babakan: Rumah Betawi Hari Ini. This research employed a descriptive qualitative approach using a practice-based research method. Data were collected through observation, interviews, literature review, and documentation conducted at the Betawi Cultural Village of Setu Babakan, South Jakarta. The findings indicate that the Director of Photography plays a significant role in translating the creative concept into visual language through the application of cinematographic techniques, including composition, shot size, camera angle, camera movement, and lighting. These techniques successfully produced communicative and aesthetically appealing visuals while strengthening the delivery of cultural messages regarding the Betawi traditional house as a representation of cultural identity. The resulting audiovisual feature is expected to function as an effective cultural communication medium to enhance public awareness, particularly among younger generations, about the importance of preserving Betawi cultural heritage.